Line balancing technique implementation in a small and medium industry - Cek Seng, Koh (2012)
The objective of this project is about the implementation of line balancing technique in a Small and Medium Industry.The implementation of line balancing in Automotive Industry has brought significant improvement to the plant's productivity.However,line balancing technique is not commonly used in Small and Medium Industry.The objective of this project is to simulate the line balancing technique and implement it in a Small and Medium Industry.The simulation was done using software called Arena where it gave overall picture of the future condition and analyze the result of production after improvement using line balancing technique. This project describes how to use line balance to save production time.Takt time and cycle time were computed with formula. The times were recorded and shorten by reducing downtime and wastes.As a result, the waiting time and total time taken were reduced.The time saved means the productivity can be increased with more time available. The waiting time has decreased around 50.81%, 50.98%, 50.76%, 50.55%, 50.88%, 50.68% and 50.77% for each extrusion machine. For each rewinding machine, the waiting time has decreased around 37.33%,36.55%, 36.12%, 35.45%, 34.86%, 34.18% and 35.76%.